Fatty Acid Composition and Nutritional Indices/Ratios of Colostrum and Milk from Crossbred Goats in the Philippines - O. Bondoc; N. A. Del Rosario; L. L. G. M. Del Rosario; D. N. Ramirez (Faculty of Animal Science, Bogor Agricultural University, 2023)
Fatty acid (FA) profiles are important measures of the nutritional quality of goat’s milk that may impact human cardiovascular health and disease. This study is aimed to compare the FA composition and FA-based nutritional indices/ratios of goat colostrum and milk from crossbred goats in relation to published reports on milk FAs involving purebred goats from other countries. A total of 121 colostrum and milk samples collected on the 30th, 60th, and 90th day of lactation from 33 crossbred goats with Anglo Nubian or Boer sires were analyzed by gas chromatography. The major FAs with the highest proportion in both colostrum and milk were oleic acid (C18:1-n9c), palmitic acid (C16:0), myristic acid (C14:0), and stearic acid (C18:0). Oleic acid, palmitic acid, and myristic acid were significantly higher (p<0.05) in colostrum than in milk (i.e., 27.4% vs 16.8%–22.9%, 24.8% vs 17.8%–19.6%, and 9.6% vs 5.2%–7.4%, respectively). Stearic acid was comparable in colostrum (8.8%) and milk (7.6%–10.8%). Total SFA and MUFA were higher in colostrum than in milk. Colostrum and milk contained low levels (less than 1.5%) of polyunsaturated fatty acids (PUFAs) – omega-6 FAs [i.e., linoleic acid C18:2 n-6 and arachidonic acid C20:4 n-6] and omega-3 FAs [i.e., α-linolenic acid C18:3 n-3 and docosahexaenoic acid C22:6 n-3]. The SFAs (C12:0, C14:0, C16:0, and C18:0) in relation to total MUFAs and PUFAs are known to contribute to the increase in cardiovascular disease. Thus, milk from crossbred goats seems to be more beneficial for cardiovascular health because of its lower atherogenicity and thrombogenicity and higher hypocholesterolemic/hypercholesterolemic ratio than those reported for several transboundary and local breeds.